2020
DOI: 10.38125/oajbs.000207
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Beliefs and Preventive Behaviours Regarding Osteoporosis Among Female Health Colleges’ Students at King Abdulaziz University

Abstract: Osteoporosis is a disease in which the density and quality of bones reduce. It is a silent thief, producing no symptoms until a fragility fracture occurs.Aim: This study aimed to assess the osteoporosis knowledge, beliefs, and preventive behaviours among female health colleges' students at King Abdulaziz University.Materials and Methods: Design: A cross sectional descriptive design. Setting and sample: 299 female students were recruited from four female health faculties (nursing, dentistry, applied medical and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…This finding is of major concern as it may prohibit early help-seeking behaviors due to an absence of symptoms. Previous research from Saudi Arabia and Malaysia has similarly indicated a lack of awareness in the general community of the 'silent' nature of osteoporosis [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is of major concern as it may prohibit early help-seeking behaviors due to an absence of symptoms. Previous research from Saudi Arabia and Malaysia has similarly indicated a lack of awareness in the general community of the 'silent' nature of osteoporosis [22,23].…”
Section: Discussionmentioning
confidence: 99%